The electronic structure calculations of two-dimensional transition-metal dichalcogenides in the presence of external electric and magnetic fields - Kuc, Agnieszka; Heine, Thomas (Chemical Society Reviews, 2015)
Transition-metal dichalcogenides TX2 (T = W, Mo; X = S, Se, Te) are layered materials that are available in ultrathin forms such as mono-, bi- and multilayers, which are commonly known as two-dimensional materials. They have an intrinsic band gap in the range of some 500 meV to 2 eV, depending on the composition and number of layers, and giant intrinsic spin-orbit splittings for odd layer numbers, and, in conjunction with their high chemical and mechanical stability, they qualify as candidate materials for two-dimensional flexible electronics and spintronics. The electronic structure of each TX2 material is very sensitive to external factors, in particular towards electric and magnetic fields. A perpendicular electric field reduces the band gap, and for some structures semiconductor-metal transitions could be possible. Moreover, the electric field triggers the spin-orbit splitting for bilayers. A magnetic field applied normal to the layers causes the Hall effect, which in some cases may result in a quantum (spin) Hall effect and thus in magnetic switches. Finally, we discuss how valleytronics is possible in these materials by selective interaction of electrons in the different valleys using polarized light.
CRIS-Team Scopus Importer:2023-03-20